Intracranial Subarachnoid Haemorrhage Caused by Cervical Spinal Dural Arteriovenous Fistulas: Case Report - Zhao, Junjie; Esemen, Yagmur; Rane, Neil; Nair, Ramesh (Frontiers in Neurology, 2021)
Cervical spinal vascular abnormalities commonly present with progressive myelopathy as a result of venous congestion. They are not very prone to bleed and tend to be underdiagnosed due to their subtle clinical presentation. We came across a rare case of intracranial subarachnoid haemorrhage caused by cervical spinal dural fistula in the Imperial College Healthcare NHS Trust Hospitals/UK in June 2020. We diagnosed the patient under strict evidence base medicine guidance, which otherwise would have been missed. We discussed the case in several multidisciplinary team (MDT) meetings, and patient was treated under the joint care of the neurology and neurosurgical teams. Patient made a full recovery and discharged home with no neurological defects or complications. Here, we reported this case with all the evidence we gathered from our MDT discussion. We hope our experience would help improve the diagnosis and management protocol for future patients with a similar condition.